Défense des classes dominantes : la division du travail de légitimation à l’épreuve des scandales financiers internationaux - Anthony Amicelle; Jean Bérard (Revue de la Régulation)
The article aims to carefully examine the reactions to the Panama Papers scandal in the light of the sociological literature on elites’ resistance to stigmas. More specifically, this article is focused on the defensive narratives of the persons targeted by the wave of revelations in the media. It also sheds light on the responses from the French government and key commentators over the French media. In this respect, we argue that this range of positions expressed on such matters largely relates to a common guiding principle contributing to the protection of the existing financial order. Indeed, the relative diversity of reactions rather refers to a division of labour – for legitimating power and domination – between the owners of economic and financial capital, the holders of State power and journalists, editorialists as well as other experts and media personalities who express their ideas in the name of their cultural capital.